2014
DOI: 10.1007/s00216-014-7914-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation ratio variability may impede clinical application of cancer diagnostic markers

Abstract: Hypermethylation at promoter regions of tumour suppressor genes is diagnostic for many cancers. Many genomic regions that may be the targets for clinical diagnostic assays have been identified through use of measuring systems reliant on bisulphite conversion, but few of these promising markers are in clinical use. The comparability of a widely used DNA methylation measuring system involving bisulphite conversion was evaluated by supplying three experienced centres with methylated DNA reference material mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Therefore, it is impossible to accurately obtain the target DNA methylation ratio and real methylation level in the samples. In fact, the target DNA methylation level in the samples is of great significance for clinical cancer diagnosis or treatment monitoring. Schmitt and co-workers reported that the breast cancer patients with a higher PITX2 DNA methylation ratio showed poor outcome after treatment with anthracycline-based chemotherapy . It is anticipated that the target DNA methylation ratio has attractive prospects in monitoring disease progression and treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is impossible to accurately obtain the target DNA methylation ratio and real methylation level in the samples. In fact, the target DNA methylation level in the samples is of great significance for clinical cancer diagnosis or treatment monitoring. Schmitt and co-workers reported that the breast cancer patients with a higher PITX2 DNA methylation ratio showed poor outcome after treatment with anthracycline-based chemotherapy . It is anticipated that the target DNA methylation ratio has attractive prospects in monitoring disease progression and treatment response.…”
Section: Introductionmentioning
confidence: 99%